PENGETAHUAN IBU BALITA DAN PERAN KADER TERHADAP PARTISIPASI IBU DALAM KEGIATAN POSYANDU BALITA DI MASA PANDEMIC COVID-19 - Nurul Aulia, Devy Lestari; Anjani, Arum Dwi; ., Endang; ., Ibrahim (Ikatan Bidan Indonesia (IBI), 2022)
Based on ministry of health strategic planning in 2015-2019, there were 80 % mothers who brought their toddlers to integrated health post in 2019. In 2020, just 55%, at Sambau Public Health Centre, there were 20,3% mothers who brought their toddlers to weigh body weight and immunizations because in March Covid-19 began to spread in Batam. The research purpose was to find out the relationship of maternal knowledge and the role of cadres against the mother’s participation in the activities of integrated health post for toddles in covid-19 pandemic. It was quantitative research. The population was toddlers’ mother at Sambau Public Health Centre. It was conducted in October 2020 – February 2021. Data collected by using questionnaire via google form link to implement large-scale restrictions inCovid-19 pandemic. The research result showed that active cadres were 17,2%, mothers’ participation in the activities of integrated health post were 85%. Based on chi-square test, p value (0,034) < α (0,05). It can be concluded that there was a relationship of maternal knowledge and mother’s participation in the activities of integrated health post for toddles in Covid-19 pandemic and there was no relationship of cadres’ role in the activities of integrated health post for toddles in covid-19 pandemic. Therefore, public health centre can improve activities of integrated health post in facing Covid-19 pandemic.